The Complexities of “Minding the Gap”: Perceived Discrepancies Between Values and Behavior Affect Well-Being - Chrystal, Megan; Karl, Johannes A.; Fischer, Ronald (Frontiers in Psychology, 2019)
Research on self-determination theory and clinical models such as acceptance and commitment therapy has shown that behaving in line with our values is key to maintaining healthy well-being. Combining work on values and experimental studies on moral hypocrisy and well-being, we experimentally tested how behaving incongruently with values affects well-being. We hypothesized that discrepancies between how one thinks one should have behaved and how one reported one did behave would be more detrimental to well-being when the behaviors were value-expressive and motivationally coherent compared to a control condition; greater perceived gaps between how participants feel they should have acted and how they report they did act would be associated with more negative well-being outcomes; the relationship between value manipulation and well-being would be mediated by perceived behavioral gap; and that personal values would interact with value manipulation to produce differential effects on well-being. One-hundred and fifty-eight first-year psychology students participated in an experiment designed to highlight discrepancies between how participants have behaved in accordance with a certain value and how they think they should have behaved, before reporting their well-being. As hypothesized, greater discrepancies between reported past behavior and how participants thought they should have behaved was associated with negative affect and decreased reports of positive well-being. We found no evidence for differential effects of manipulated value-expressive behaviors on well-being, or for our hypotheses that personal values and manipulated value-expressive behaviors interact. Nevertheless, value content mattered in terms of inducing perceived behavioral gaps. Our study suggests that perceived discrepancies between any value and reported past behavior can have a negative impact on some aspects of well-being. We discuss how the application of our methodology can be used in further studies to disentangle the value-behavior nexus.